Single-Chip 19 and 24 GHz VCO and Frequency Divider Fabricated in a Commercial SiGe Bipolar Technology - Ettinger, Klaus; Stelzer, Andreas; Höftberger, Josef; Diskus, Christian; Fenk, Josef; Weigel, Robert (Microwave Conference, 2002. 32nd European, 2002)
This paper presents the design, implementation and testing of fully integrated 19 and 24 GHz voltage controlled oscillator chips for RADAR distance sensor applications. The oscillators are integrated on one chip together with a frequency divider with a divide ratio of 16 and 32, as well as an output driver. The chips are fabricated in a production SiGe bipolar technology and have an area of 960 Ã Â 960 Ã Â¿m2 each. Both VCOs are varactor-tuned LC-type oscillators with a tuning range of about 1 GHz featurng different inductors and transistors. Both chips work from a single 3.6 V supply, the 24 GHz VCO draws 6 mA and the 19 GHz VCO draws 9 mA of supply current, respectively. Divider and output driver consume 23 mA and 51 mA, respectively. The measured phase-noise of the 19 GHz VCO is about Ã Â¿100 dBc/Hz at 1 MHz offset frequency, whereas the 24 GHz VCO features a phase-noise of about Ã Â¿89 dBc/Hz.
elib2cris::1512001600,ettinger2002a
Keywords: Driver Circuits; Frequency Conversion